Optimization of extracellular matrix production from human induced pluripotent stem cell‐derived fibroblasts for scaffold fabrication for application in wound healing. Issue 10 (23rd March 2021) - Marinkovic, Milica; Sridharan, Rukmani; Santarella, Francesco; Smith, Avi; Garlick, Jonathan A.; Kearney, Cathal J.
Abstract: Extracellular matrix is a key component of all tissues, including skin and it plays a crucial role in the complex events of wound healing. These events are impaired in chronic wounds, with chronic inflammation and infection often present in these non‐healing wounds. Many tissue engineering approaches for wound healing provide a scaffold to mimic the native matrix. Fibroblasts derived from iPS cells (iPSF) represent a novel source of matrix rich in pro‐regenerative components, which can be used for scaffold fabrication to improve wound healing. However, in vitro production of matrix by cells for scaffold fabrication requires long cell culturing times which increases cost. The aim of this work is to optimize the iPSF matrix production by boosting matrix deposition, without affecting its composition. A good candidate technique to achieve this goal is macromolecular crowding, which is known to promote conversion of procollagen into mature collagen and its accumulation. We tested two molecular crowders, Ficoll and Carrageenan—in combination with ascorbic acid—over a prolonged period of time. Ficoll in combination with ascorbic acid notably increased collagen deposition and matrix dry weight compared to ascorbic acid alone, and did not affect matrix composition as measured by RT‐PCR. Interestingly, Carrageenan did not affect collagen quantity, but it significantly increased glycosaminoglycan deposition. Finally, we successfully fabricated scaffolds from harvested matrix and confirmed their ability for cell growth and viability. This work lays the foundation for development of a time and cost effective protocol for novel iPSF ECM production for tissue engineering scaffolds.